Impactor flux and cratering on the Pluto-Charon system - Elía, Gonzalo Carlos de (2010)
Aims. We study the impactor flux and cratering on Pluto and Charon caused by the collisional evolution of Plutinos. Plutinos are trans-Neptunian objects located at ∼39.5 AU, in the 3:2 mean motion resonance with Neptune. Methods. We develop a statistical code that includes catastrophic collisions and cratering events, and takes into account the stability and instability zones of the 3:2 mean motion resonance with Neptune. Our numerical algorithm proposes different initial populations that account for the uncertainty in the size distribution of Plutinos at small sizes. Results. Depending on the initial population, our results indicate the following. The number of D > 1 km Plutinos streaking Pluto over 3.5 Gyr is between 1271 and 5552. For Charon, the number of D > 1 km Plutino impactors is between 354 and 1545. The number of D > 1 km craters on Pluto produced by Plutinos in the past 3.5 Gyr is between 43 076 and 113 879. For Charon, the number of D > 1 km craters is between 20 351 and 50 688. On the other hand, the largest Plutino impactor onto Pluto has a diameter of between ∼17 and 23 km, which produces a crater with a diameter of ∼31-39 km. In the same way, the largest Plutino impactor onto Charon has a diameter of between ∼10 and 15 km, which produces a crater with a diameter of ∼24-33 km. Finally, we test the dependence of results on the number of Pluto-sized objects in the Plutino population. If two Pluto-sized objects are assumed in the 3:2 Neptune resonance, the total number of Plutino impactors onto both Pluto and Charon with diameters D > 1 km is a factor of ∼1.6-1.8 larger than that obtained considering only one Pluto-sized object in this resonant region. Conclusions. Given the structure of the trans-Neptunian region, with its dynamically different populations, it is necessary to study in detail the contribution of all the potential sources of impactors onto the Pluto-Charon system, to determine the main contributor and the whole production of craters. Then, we will be able to contrast those studies with observations, which will help us to understand the geological processes and history of the surface of those worlds.